2016
DOI: 10.4103/2231-0762.192938
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral health education in the form of Braille and oral health talk on oral hygiene knowledge, practices, and status of 12–17 years old visually impaired school girls in Pune city: A comparative study

Abstract: Aim:To assess the effect of oral health education (OHE) in the form of Braille and combination with Oral health talk (OHT) on oral hygiene knowledge, practices, and status of 12–17 years old visually impaired school girls in Pune city.Materials and Methods:A 6-week comparative study was conducted among 74 residential visually impaired school girls aged 12–17 years, who were trained to read Braille. The participants were divided into two groups, namely, Group A (n = 37) receiving OHE only in the form of Braille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(56 citation statements)
references
References 10 publications
2
54
0
Order By: Relevance
“…All the children were then given one-to-one oral hygiene education and motivation by the institution teachers so that they could learn proper brushing skills. 38 Similar results were seen in a study conducted by Bhor et al 13 that compared effectiveness of oral health education by means of Braille booklets only and combined effect of Braille booklet and oral health talks. The results showed that oral health education in both forms, Braille and combination of Braille and oral health talks, was instrumental in improving the oral health knowledge, oral hygiene status, and practices of these children but continuous reinforcement in form of oral health talks showed better results.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…All the children were then given one-to-one oral hygiene education and motivation by the institution teachers so that they could learn proper brushing skills. 38 Similar results were seen in a study conducted by Bhor et al 13 that compared effectiveness of oral health education by means of Braille booklets only and combined effect of Braille booklet and oral health talks. The results showed that oral health education in both forms, Braille and combination of Braille and oral health talks, was instrumental in improving the oral health knowledge, oral hygiene status, and practices of these children but continuous reinforcement in form of oral health talks showed better results.…”
Section: Discussionsupporting
confidence: 65%
“…Similar results were observed in the study conducted by Hebbal and Ankola, 32 in which subjects who brushed twice daily increased to 58.3% after health education as compared to 45.8% subjects who brushed once daily before health education. 2 Similarly, in a study conducted by Bhor et al, 13 the frequency of toothbrushing increased from once to twice daily after implementation of oral health educational program.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Bhor et al [17] evaluated the effect of oral health education using Braille instructions in combination with discussions on oral hygiene techniques. The effect of Braille instructions and audio recordings on the level of oral hygiene of blind institutionalised children has been studied by Mahantesha et al [18] At the beginning, the children's oral health knowledge was poor due to their institutional background, where they had received no information about the importance or oral hygiene.…”
Section: Resultsmentioning
confidence: 99%
“…The study was conducted in the course of 8 weeks. [6][7][8][9][10] First Visit (Interactive Session)…”
Section: • Children With Any Other Disability • Children Who Could Nomentioning
confidence: 99%